2013
DOI: 10.1111/head.12258
|View full text |Cite
|
Sign up to set email alerts
|

One‐Day Behavioral Intervention in Depressed Migraine Patients: Effects on Headache

Abstract: Objective To determine whether a 1-day behavioral intervention, aimed at enhancing psychological flexibility, improves headache outcomes of migraine patients with comorbid depression. Background Migraine is often comorbid with depression, with each disorder increasing the risk for onset and exacerbation of the other. Managing psychological triggers, such as stress and depression, may result in greater success of headache management. Method Sixty patients with comorbid migraine and depression were assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…The effects for depression were larger than for headaches, consistent with the trial by Dindo and colleagues (Dindo et al, 2014(Dindo et al, , 2012. The mean BDI-II score of the treatment group at baseline of 30.6 falls in the 'severe depression' category, and the mean score at post-treatment of 13.1 falls in the 'minimal to mild depression' category and below the cut-off for 'may need treatment' of 17.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The effects for depression were larger than for headaches, consistent with the trial by Dindo and colleagues (Dindo et al, 2014(Dindo et al, , 2012. The mean BDI-II score of the treatment group at baseline of 30.6 falls in the 'severe depression' category, and the mean score at post-treatment of 13.1 falls in the 'minimal to mild depression' category and below the cut-off for 'may need treatment' of 17.…”
Section: Discussionsupporting
confidence: 82%
“…The latter finding is unique as the only previous trial of an integrated treatment for comorbid headaches and depression failed to find a significant difference between headache changes in the treatment and control groups (Dindo et al, 2014). The reason for the different findings between the studies is not clear but the two studies did use quite different behavioral interventions as the intervention in Dindo et al was a one-day Acceptance and Commitment Training plus Migraine Education workshop, as distinct from the 12 weekly 50-min sessions of CBT based on a functional model used in this study.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…There were no significant differences in treatment outcomes between groups. In another study, researchers assigned patients with comorbid migraine and depression to either a 1-day ACT training plus migraine education workshop or to treatment as usual [17]. The results suggested that participants in the experimental condition demonstrated significant improvements in reducing headache frequency, headache severity, medication use, and headacherelated disability, while the control group did not demonstrate improvements in these outcomes.…”
Section: Cognitive and Behavioral Treatmentsmentioning
confidence: 99%